Comparative karyotype analysis of the red brocket deer (M. americana sensu lato and M. rufa) complex: evidence of drastic chromosomal evolution and implications on speciation process - Bernegossi, Agda Maria; Galindo, David Javier; Peres, Pedro Henrique Faria; Vozdova, Miluse; Cernohorska, Halina; Kubickova, Svatava; Kadlcikova, Dita; Rubes, Jiri; Duarte, José Maurício Barbanti (Journal of applied genetics, 2024)
Chromosomal rearrangements are often associated with playing a role in the speciation process. However, the underlying mechanism that favors the genetic isolation associated with chromosomal changes remains elusive. In this sense, the genus Mazama is recognized by its high level of karyotype diversity among species with similar morphology. A cryptic species complex has been identified within the genus, with the red brocket deer (Mazama americana and Mazama rufa) being the most impressive example. The chromosome variation was clustered in cytotypes with diploid numbers ranging from 42 to 53 and was correlated with geographical location. We conducted an analysis of chromosome evolution of the red brocket deer complex using comparative chromosome painting and Bacterial Artificial Chromosome (BAC) clones among different cytotypes. The aim was to deepen our understanding of the karyotypic relationships within the red brocket, thereby elucidating the significant chromosome variation among closely related species. This underscores the significance of chromosome changes as a key evolutionary process shaping their genomes. The results revealed the presence of three distinct cytogenetic lineages characterized by significant karyotypic divergence, suggesting the existence of efficient post-zygotic barriers. Tandem fusions constitute the main mechanism driving karyotype evolution, following a few centric fusions, inversion X-autosomal fusions. The BAC mapping has improved our comprehension of the karyotypic relationships within the red brocket deer complex, prompting questions regarding the role of these changes in the speciation process. We propose the red brocket as a model group to investigate how chromosomal changes contribute to isolation and explore the implications of these changes in taxonomy and conservation.
Keywords: molekulární evoluce; Chromosome evolution; vznik druhů (genetika); Chromosome Painting; Genetic Speciation; karyotyp; karyotypizace; Evolution, Molecular; vysoká zvěř; Karyotype; Karyotyping; Neotropical deer, Cervidae; Chromosome rearrangements; FISH; zvířata; malování chromozomů; Chromosomes, Artificial, Bacterial; Deer; Molecular cytogenetics; umělé bakteriální chromozomy; Animals